Analysis of Tax Collection with Reprimand and Forced Letters at the North Makassar - Sudirman, Sitti Rahma; Rinaldi, Muhammad; Khatib Ramadhani , Muhammad Harits Zidni (Eastasouth Institute, 2023)
This study examines the efficacy of tax collection using reprimand letters and forced letters at KPP Pratama Makassar Utara to discharge tax arrears. This study is based on the fact that the desired amount of tax income and collection varies yearly, implying that many taxpayers fail to meet their tax responsibilities, resulting in tax arrears. This study uses a descriptive analysis method to provide an overview of whether tax collection with a reprimand and forced letters have been effective at KPP Pratama Makassar Utara. The source of data used in this study is in the form of secondary data. Namely, the data obtained is processed data from the relevant agency and the data used to support the study's results. The research data obtained were analyzed using descriptive ratio analysis. The ratio analysis used is the effectiveness ratio. The results of this study show that the effectiveness of tax collection with reprimand letters in 2014-2017 is classified as ineffective and forced letters in 2014-2017 are classified as effective. This study relied on secondary data as its source of information. Specifically, the data gathered is processed data from the appropriate agency, and the data is utilized to support the study's findings. The collected research data were examined using descriptive ratio analysis. The effectiveness ratio was employed in the ratio analysis. According to the results of this study, the efficacy of tax collection with reprimand letters in 2014-2017 is categorized as ineffective, whereas the effectiveness of tax collection with forced notes in 2014-2017 is classed as effective.